Improving the Competence of Elementary School Teachers in Child-Friendly Sexual Education through a Statistics Based Workshops and Effective Practices - Mukhti, Tessy Octavia; Yusra, Zulmi Yusra; Sari, Widia Kemala; Taslim, Fauziah (Fakultas MIPA Universitas Negeri Padang, 2025)
Sexual violence against children is a serious issue requiring comprehensive prevention efforts. Data from the Ministry of Women’s Empowerment and Child Protection indicate an increase in cases from 2020 to 2024, highlighting the urgency of sexual education at the elementary school level. However, teachers in Gugus 2, Kecamatan VI Koto, Kabupaten Agam face limited access to updated training and resources on sensitive topics such as sexuality. This community service activity aimed to enhance teachers’ knowledge, attitudes, and readiness in delivering child-friendly sexual education. The program was implemented in five stages: socialization, observation with interviews, material provision, technology application, and evaluation. Results showed improved teacher understanding and skills in teaching sexual education through a phased approach introducing body privacy, recognizing dangers, and developing self-protection. The integration of digital media, such as Canva-based infographics and interactive coding, further supported learning effectiveness. Evaluation indicated increased teacher comprehension across all topics.